2007
DOI: 10.1203/pdr.0b013e3180db291b
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Regional Evolution of Aquaporin-4 Expression and Magnetic Resonance Imaging in a Rat Pup Model of Neonatal Stroke

Abstract: Edema formation can be observed using magnetic resonance imaging (MRI) in patients with stroke. Recent studies have shown that aquaporin-4 (AQP4), a water channel, is induced early after stroke and potentially participates in the development of brain edema. We studied whether induction of AQP4 correlated with edema formation in a rat pup filament stroke model using high field (11.7-Tesla) MRI followed by immunohistochemical investigation of AQP4 protein expression. At 24 h, we observed increased T2 values and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 20 publications
5
70
3
1
Order By: Relevance
“…In young rats, AQP4 expression was increased 24 h after stroke at the edge of the lesion where there was no significant modification of water content measured by magnetic resonance imaging (Badaut et al, 2007a), suggesting that increased AQP4 expression could limit or prevent the formation and extension of edema. The role of AQP4 in cerebral edema is dual and depends of the model used (Badaut et al, 2007b;Verkman et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…In young rats, AQP4 expression was increased 24 h after stroke at the edge of the lesion where there was no significant modification of water content measured by magnetic resonance imaging (Badaut et al, 2007a), suggesting that increased AQP4 expression could limit or prevent the formation and extension of edema. The role of AQP4 in cerebral edema is dual and depends of the model used (Badaut et al, 2007b;Verkman et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…AQP4 expression has also been observed at 48 h in transient occlusions. In a mild stroke model (30 min of MCA occlusion), up-regulated AQP4 expression was detected for up to 7 d, whereas in a severe stroke model, elevated AQP4 expression persisted for up to 28 d [32,33] . The pattern of AQP4 expression in cerebrovascular diseases has revealed that this molecule plays a critical role in regulating water movement during brain edema [17] .…”
Section: Discussionmentioning
confidence: 99%
“…NF200, MBP, and CNPase coronal sections that were immunostained with infrared secondary antibodies were scanned using the same parameters for sham and CCI with a Licor-Odyssey scanner at 21 lm/pixel resolution (Licor BioScience, Lincoln, NE). The infrared method proposed to quantify the immunohistochemistry has recently been described by different authors (Bloch et al, 2011;Wong, 2004), and by our group (Badaut et al, 2007(Badaut et al, ,2011. For surface area measurements of the CC with NF200 (see Fig.…”
Section: Tissue Processing and Immunohistochemistrymentioning
confidence: 99%